2012
DOI: 10.1086/667226
|View full text |Cite
|
Sign up to set email alerts
|

Commitment and Behavior Change: Evidence from the Field

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
178
1
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(192 citation statements)
references
References 54 publications
(47 reference statements)
5
178
1
8
Order By: Relevance
“…In addition, if consumers are sympathetic to sustainable issues, this suggests that their behaviour could be steered towards more pro-environmental actions, or that the right types of marketing appeals (communications) could be effective in eliciting more sustainable consumption behaviour (Mair & Bergin-Seers, 2010). The mix and type of interventions or messages is important and can dramatically increase (or decrease) the effectiveness of pro-environmental appeals (BacaMotes, Brown, Gneezy, Keenan, & Nelson, 2013).…”
Section: The Market Development Approachmentioning
confidence: 99%
“…In addition, if consumers are sympathetic to sustainable issues, this suggests that their behaviour could be steered towards more pro-environmental actions, or that the right types of marketing appeals (communications) could be effective in eliciting more sustainable consumption behaviour (Mair & Bergin-Seers, 2010). The mix and type of interventions or messages is important and can dramatically increase (or decrease) the effectiveness of pro-environmental appeals (BacaMotes, Brown, Gneezy, Keenan, & Nelson, 2013).…”
Section: The Market Development Approachmentioning
confidence: 99%
“…To some extent, there is certain progress in changing behavior and research has shown that with adequate measures (e.g., individual consulting, commitment strategies, campaigns making use of social norms etc.) applied at the right time (e.g., windows of opportunity where habits can be broken), behavior can actually be changed Schäfer et al, 2012;Baca-Motes et al, 2013). However, societies are not yet really on track with the ambitious goals they aspire to.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is a vast amount of literature in the consumer behavior field devoted to examining the effectiveness of softer motivators applied by social marketers to foster energy conserving behavior, including social norms, commitment strategies, prompts, or soft nudges (e.g., Aronson and O'Leary, 1982;McCalley, 2006;Schäfer et al, 2012;Baca-Motes et al, 2013;Burchell et al, 2013;Sunstein and Reisch, 2013). Other streams of research are devoted to analyzing new less resource-intensive models of consumption such as collaborative consumption (e.g., Botsman and Rogers, 2010;Belk, 2010;Ozanne and Ballantine, 2010;Bardhi and Eckhardt, 2012) and the relationship between materialism and happiness (e.g., Burroughs and Rindfleisch, 2002).…”
Section: Ecb and Its Change From A Consumer Behavior Perspectivementioning
confidence: 99%
“…On the other hand, studies by other researchers such as Levine and Strube (2012), Baca -Motes et al (2012), and the Aytekin and Buyukahraz (2013) measure the influences of social, demography, knowledge and individual on the transformation of behaviour of their respondents towards environmental sustainability. Levine and Strube (2012) found that knowledge is closely related to behaviour.…”
Section: (A) Pra-kitar Semula Guna Semula Dan Kitar Semula Adalah Jementioning
confidence: 99%
“…Attitude clearly influenced the intention, and the intention had a strong relationship with behaviour. Baca-Motes et al (2012) found that attitudes and behaviours operate through separate routes to affect environmentally friendly behaviour. Therefore, this study suggests that interventions, using different mechanisms, targeting both knowledge and attitude will clearly link to behaviour change.…”
Section: (A) Pra-kitar Semula Guna Semula Dan Kitar Semula Adalah Jementioning
confidence: 99%